2017
DOI: 10.1002/lio2.94
|View full text |Cite
|
Sign up to set email alerts
|

Chicken thigh microvascular training model improves resident surgical skills

Abstract: ObjectivesMicrosurgical techniques are essential for vessel anastomosis in free flap reconstructive surgery. However, teaching these skills intraoperatively is difficult. The chicken thigh microvascular model is a high‐fidelity model that has been previously validated to differentiate between skill levels of surgeons. This study aims to determine if this model objectively improves microsurgical skills.Study DesignValidation studyMethodsThirteen residents were given a tutorial on microvascular anastomosis and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…The chicken thigh model has demonstrated objective improvement in microvascular skills and a significant decrease in anastomosis time. 18 20 In this model, there was a statistically significant decrease between the time required to complete the first stitch (235 seconds, 95% confidence interval, 198–272 seconds) and the time required to complete the last stitch (120 seconds; 95% confidence interval, 92–149 seconds), an average 48.7% (115 seconds) decrease in time ( P < 0.001). Junior (postgraduate year 2–3) and senior (postgraduate year 4–5) residents had similar decreases in time (49.1% and 48.21%, respectively).…”
Section: Microsurgery Training Modelsmentioning
confidence: 82%
See 2 more Smart Citations
“…The chicken thigh model has demonstrated objective improvement in microvascular skills and a significant decrease in anastomosis time. 18 20 In this model, there was a statistically significant decrease between the time required to complete the first stitch (235 seconds, 95% confidence interval, 198–272 seconds) and the time required to complete the last stitch (120 seconds; 95% confidence interval, 92–149 seconds), an average 48.7% (115 seconds) decrease in time ( P < 0.001). Junior (postgraduate year 2–3) and senior (postgraduate year 4–5) residents had similar decreases in time (49.1% and 48.21%, respectively).…”
Section: Microsurgery Training Modelsmentioning
confidence: 82%
“…The classic specimens used for training are chicken, rat, and porcine models. 18 – 28 Chicken specimens are readily available and inexpensive, making them a popular choice for microsurgery simulation. The chicken aorta, which measures approximately 4 mm in diameter, has been reported to be effective to practice microvascular anastomosis.…”
Section: Microsurgery Training Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since most identified models were not supported by a great number of validation studies, they received a lower LoR. The cryopreserved rat aorta model(Kim et al, ; Ghanem et al, ) which used anastomosis lapse index tool for skills assessment was the only model, overall, to receive a LoR of 1, with chicken thigh(Creighton et al, ; Schoeff et al, ) and chicken wing(Jusue‐Torres et al, ; Kaplan et al, ) models receiving a LoR of 2. Similar to animal cadaveric tissue models, human cadaveric tissue models have also been used and are considered superior to animal cadaveric models in terms of offering correct anatomy, consistency and similar texture of the tissue to humans.…”
Section: Discussionmentioning
confidence: 99%
“…The chicken aorta model (Ramachandran et al, ) owing to its large lumen size (4 mm) is suitable to help build confidence in the novice microsurgeons. The chicken thigh model (Creighton et al, ; Schoeff et al, ; Pafitanis et al, ) demonstrated objective improvement in the microvascular surgical skills of the residents and a significant reduction in the time required to complete the anastomosis. Jeong et al () found that using the femoral neurovascular bundle of the chicken leg to practice the microanastomosis also demonstrated efficiency in anastomosis performance.…”
Section: Animal Cadaveric Tissue Modelsmentioning
confidence: 99%